Innovation of Goat's Milk Soft Candy with Annatto Extract (bixa orellana l.) As Natural Colorant and Antioxidant - Dewi, Yohana Sutiknyawati Kusuma; Putri, Dea Malyana; Fadly, Dzul; Rahmalia, Winda (Department of Technology of Agricultural product (THP) Jambi University, 2023)
The research aims to produce innovative soft candy from goat's milk and annatto extract as colorants and antioxidants that consumers like. Soft candy product innovations were studied in random group designs consisting of five concentrations of annatto extract (0%, 0.15%, 0.20%, 0.25%, and 0.30%). The results showed that the addition of annatto extract in the goat's milk soft candy formula decreases the L value, along with an increase of a* and b values so that the color of the soft candy becomes orange. Increasing the concentration of annatto extract causes a significant increase in antioxidant activity. The addition of annatto extract in the goat's milk candy formulation influenced the level of preference for the color attribute but did not affect the aroma, taste, and texture attributes. The goat's milk soft candy with the addition of 30% annatto extract as a natural colorant and antioxidant produced the best physicochemical and sensory characteristics based on index effectivity value. This soft candy resulted in a water content of 7.46±0.74%, ash content of 0.57±0.07%, and antioxidant activity of 69.20±1.07%. The addition of annatto extract also does not affect the ash content or water content of the goat's milk soft candy produced.